2010
DOI: 10.3892/mmr.2010.389
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of endothelial cell migration through the down‑regulation of MMP-9 by A-kinase anchoring protein 12

Abstract: Abstract. Matrix metalloproteinases (MMPs) play an important role in the degradation of extracellular matrix (ecM) molecules. ecM degradation is associated with tumor metastasis and angiogenesis. Therefore, the regulation of MMPs is of potential benefit in the treatment of various diseases, including cancer. a-kinase anchoring protein 12 (aKaP12) has been identified as a potential tumor suppressor. However, the function of aKaP12 as a tumor suppressor is not well understood. Herein, to determine the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…We found in the current report that gravin-t/t mice showed decreased MMP-9 expression in aortic sections, which could potentially explain the reduced atherosclerotic vascular remodeling and plaque formation. Activation of macrophage and increased expression of MMPs have been shown to contribute to the development of human atherosclerotic lesions (21,35). It has also been shown that overexpression of gravin downregulates the expression of MMP-9 in a carcinogenic cell line, where MMP-9 is involved in endothelial cell migration via downregulation of activator protein-1 and its transcriptional activity (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found in the current report that gravin-t/t mice showed decreased MMP-9 expression in aortic sections, which could potentially explain the reduced atherosclerotic vascular remodeling and plaque formation. Activation of macrophage and increased expression of MMPs have been shown to contribute to the development of human atherosclerotic lesions (21,35). It has also been shown that overexpression of gravin downregulates the expression of MMP-9 in a carcinogenic cell line, where MMP-9 is involved in endothelial cell migration via downregulation of activator protein-1 and its transcriptional activity (35).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of macrophage and increased expression of MMPs have been shown to contribute to the development of human atherosclerotic lesions (21,35). It has also been shown that overexpression of gravin downregulates the expression of MMP-9 in a carcinogenic cell line, where MMP-9 is involved in endothelial cell migration via downregulation of activator protein-1 and its transcriptional activity (35). A possible explanation for gravin's distinct roles in regulating MMPs may instead be related to the different substrates' specificities between the endothelial cell and VSMCs.…”
Section: Discussionmentioning
confidence: 99%
“…EPB41L2, AKAP12, FABP3, SCRN-1, CDV3 and are thus of high relevance and certainty. The A-kinase anchor protein 12 (AKAP12) has a pivotal role in regulation of cellular adhesion dynamics and is also a putative inhibitor of angiogenesis through down-regulation of MMP9 expression [54]. MMP9 inhibition through AKAP12 may thus suppress the typical hallmarks of OA in the LM scored individual i.e.…”
Section: Discussionmentioning
confidence: 99%
“…MMP can directly degrade the ECM as well as digest the BM ( Cardoso et al, 2010 ). Studies found an increased expression of MMP upon LPS treatment, which was accompanied by increased permeability of BBB ( Tilling et al, 1998 ; Yang et al, 2007 ; Vanlaere and Libert, 2009 ; Cardoso et al, 2010 ; Coisne and Engelhardt, 2011 ; Lee et al, 2011 ; Zhao et al, 2011 ; Qin et al, 2015 ).…”
Section: Direct Effectsmentioning
confidence: 99%